2010
DOI: 10.2140/ant.2010.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Equations for Chow and Hilbert quotients

Abstract: We give explicit equations for the Chow and Hilbert quotients of a projective scheme X by the action of an algebraic torus T in an auxiliary toric variety. As a consequence we provide geometric invariant theory descriptions of these canonical quotients, and obtain other GIT quotients of X by variation of GIT quotient. We apply these results to find equations for the moduli space M 0,n of stable genus-zero n-pointed curves as a subvariety of a smooth toric variety defined via tropical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 34 publications
0
43
1
Order By: Relevance
“…However, the connection between the algebraic and tropical moduli spaces runs much deeper. Building on previous work of Tevelev [24], Gibney and Maclagan [11] exhibit M trop 0,n as a tropicalization. They find an embedding of M 0,n into a torus, such that the tropicalization of M 0,n is a balanced fan Σ, such that Σ ∼ = M trop 0,n .…”
Section: Context and Motivationmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the connection between the algebraic and tropical moduli spaces runs much deeper. Building on previous work of Tevelev [24], Gibney and Maclagan [11] exhibit M trop 0,n as a tropicalization. They find an embedding of M 0,n into a torus, such that the tropicalization of M 0,n is a balanced fan Σ, such that Σ ∼ = M trop 0,n .…”
Section: Context and Motivationmentioning
confidence: 70%
“…Fix this fan structure. Then we have the following result, due to Gibney and Maclagan [11,Theorem 5.7], as well as Tevelev [24,Theorem 5.5]. THEOREM 3.1.…”
Section: Tropicalizing Spaces Of Rational Weighted Stable Curvesmentioning
confidence: 81%
“…This also rules out rational equivalence (as defined in [1]): two cycles are equivalent, if and only if their recession fans are equal.But there is another, coarser equivalence on M trop 0,n that comes from toric geometry. As was shown in[20], the classical M 0,n can be embedded in the toric variety X (M n )) ∼ = Pic(M 0,n ) D I → δ I ,…”
mentioning
confidence: 69%
“…A much stronger relation was proven in [20], where it is shown that (for the right embedding) the tropicalization of M 0,n is M The ith Psi class is the subset ψ i of M 0,n , consisting of the locus of all n-marked curves such that the ith leaf is attached to a vertex that is at least four-valent.…”
Section: Remark 27mentioning
confidence: 94%
“…. , T r2 ] and vice versa, we use the following operations, compare also [21]. Consider a homomorphism π : T r → T n of tori and its kernel H ⊆ T r .…”
Section: Basic Algorithmsmentioning
confidence: 99%